Microbial incidence in acute pharyngitis using throat swab analysis - Umar, Mumtaz Ahmad; Baig, Mirza Nasheed; Jawad, Ayesha; Mushwani, Mohibullah; Iftikhar, Saira; Arshad, Naveed (Journal of Rawalpindi Medical College, 2025)
Background & Objective: The inflammatory response of mucous membrane in the oropharynx is acute pharyngitis, often due to infection by various microorganisms, including fungi, virus, and bacteria. The study objective was to identify the spectrum of microorganisms responsible for acute pharyngitis through analysis of throat swab specimens. Methods: A cross-section observational analysis was conducted at the ENT Department of Akbar Niazi Teaching Hospital, Islamabad, between February and July 2023. The study comprised a total of 100 patients diagnosed with acute pharyngitis. Throat swabs were aseptically collected from all patients and sent for culture. The microorganisms were identified using biochemical procedures, and their susceptibility to antimicrobic agents was determined using conventional techniques. SPSS v 25 was used for data analysis. Results: Microorganisms were identified in 30 out of 100 specimens, with no growth observed in the remaining 70 specimens. The most commonly identified organism was Streptococcus pyogenes, found in 90% (n=27) of cases, subsequently Staphylococcus aureus at 60% (n=18) and Candida albicans at 13% (n=4). In 43.3% of cases, a solitary pathogen, Streptococcus pyogenes in 12 cases (92.3%) and Staphylococcus aureus in 1 (7.7%) were identified. The remaining 56.7% of culture reports indicated mixed infections. Conclusion: It was found that Streptococcus pyogenes and Staphylococcus aureus were the primary causes of single infection, whereas Candida albicans, in conjunction with bacteria, was isolated in cases of mixed infections.